Sins of the fathers: The intergenerational legacy of the 1959-1961 Great Chinese Famine on children's cognitive development - Tan, Chih Ming; Tan, Zhibo; Zhang, Xiaobo (International Food Policy Research Institute, 2014)
The intergenerational effect of fetal exposure to malnutrition on cognitive ability has rarely been studied for human beings in large part due to lack of data. In this paper, we exploit a natural experiment, the Great Chinese Famine of 1959–1961, and employ a novel dataset, the China Family Panel Studies, to explore the intergenerational legacy of early childhood health shocks on the cognitive abilities of the children of parents born during the famine. We find that daughters born to rural fathers who experienced the famine in early childhood score lower in major tests than sons, whereas children born to female survivors are not affected.